2017
DOI: 10.1002/2017gl073592
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary JIRAM results from Juno polar observations: 3. Evidence of diffuse methane presence in the Jupiter auroral regions

Abstract: Throughout the first orbit of the NASA Juno mission around Jupiter, the Jupiter InfraRed Auroral Mapper (JIRAM) targeted the northern and southern polar regions several times. The analyses of the acquired images and spectra confirmed a significant presence of methane (CH4) near both poles through its 3.3 μm emission overlapping the H3+ auroral feature at 3.31 μm. Neither acetylene (C2H2) nor ethane (C2H6) have been observed so far. The analysis method, developed for the retrieval of H3+ temperature and abundan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…More details on the analysis and the relative discussion about the presence of methane auroral emissions are matter of a separate paper by Moriconi et al . [].…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More details on the analysis and the relative discussion about the presence of methane auroral emissions are matter of a separate paper by Moriconi et al . [].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…In the same figure the dashed curves show the respective modeled spectra used to determine the H 3 + temperature and the column density. More details on the analysis and the relative discussion about the presence of methane auroral emissions are matter of a separate paper by Moriconi et al [2017]. Figure 4 shows the H 3 + temperature field, whose values range between 850°K and 1100°K.…”
Section: 1002/2017gl072905mentioning
confidence: 99%
“…The image intensity is adjusted (multiplied by the cosine of the emission angle), assuming that radiance is constant along such column, to normalize the measured radiance to that coming from a vertical column. This also implies that there is no methane absorption above the H 3 + emission region; in fact, the spectrometer measurements of the auroral region (made with the same viewing geometry of the imager) show that even where the methane emission is large, it is always superimposed to the H 3 + spectrum, this indicates that the two molecules either coexist at the same altitudes or the methane layer is below the H 3 + layer [ Dinelli et al ., ; Adriani et al ., ; Moriconi et al ., ]. The image intensity is not the total H 3 + emission, but only the segment in the filter passband.…”
Section: Data Processingmentioning
confidence: 99%
“…This paper is the first of three papers where we report the observations of the Jupiter auroras made with the spectrometer of JIRAM: here we describe the methodology used to analyze JIRAM spectra of the auroral regions, and we report the results obtained for the Jupiter northern polar region. Further results obtained for both the auroral regions are reported in Adriani et al [2017] and Moriconi et al [2017].…”
Section: Introductionmentioning
confidence: 62%
“…Considering that methane has already been observed in Jupiter auroral region [Altieri et al, 2016] and its 3 Q-branch lies in the same spectral region, we simulated the analyzed spectral region adding the methane emission around 3.3 μm. A quick comparison of the simulated spectra with our measurements showed that the recorded signal was compatible with the CH 4 emission at 500 K superimposed to the H + 3 spectrum [see Moriconi et al, 2017]. We therefore repeated the analysis of all the spectra including the CH 4 column density among the target parameters, keeping its effective temperature fixed at 500 K. Indeed, this inclusion reduced the test value of the retrieval.…”
Section: Discussionmentioning
confidence: 88%